2014
DOI: 10.1074/jbc.m114.580167
|View full text |Cite
|
Sign up to set email alerts
|

Protein Degradation and Quality Control in Cells from Laforin and Malin Knockout Mice

Abstract: Background: Lafora disease involves impaired glycogen metabolism and protein degradation. Results: Impaired proteasomal degradation and mTOR-dependent autophagy in the absence of laforin or malin but decreased LAMP1 and GABARAPL1, perhaps indicative of defective lysosomal glycogen trafficking, only in malin deficiency. Conclusion: We speculate that defective protein degradation and quality control might be secondary to glycogen accumulation. Significance: Identification of a malin function independent of lafor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
(40 reference statements)
2
23
0
Order By: Relevance
“…Therefore, we wanted to test if the heat shock-induced clearance of polyubiquitinated proteins is effective in the absence of laforin or malin. Corroborating earlier reports (Aguado et al 2010;Puri et al 2012, Criado et al 2012Singh et al 2013;Garyali et al 2014), we found that cells partially silenced for laforin and malin have higher level of polyubiquitinated proteins, compared to the control (Fig. 3a).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Therefore, we wanted to test if the heat shock-induced clearance of polyubiquitinated proteins is effective in the absence of laforin or malin. Corroborating earlier reports (Aguado et al 2010;Puri et al 2012, Criado et al 2012Singh et al 2013;Garyali et al 2014), we found that cells partially silenced for laforin and malin have higher level of polyubiquitinated proteins, compared to the control (Fig. 3a).…”
Section: Resultssupporting
confidence: 76%
“…Malin and laforin are necessary for autophagic induction and loss of either result in autophagy blockade (Aguado et al 2010;Puri et al 2012, Criado et al 2012Singh et al 2013;Garyali et al 2014). The Neuro2a cells used in the present study also showed a similar effect upon a transient loss of laforin or malin (Fig.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…However, several reports have connected loss of laforin with decreased autophagy, which could have a role in glycogen disposal (42)(43)(44)(45)(46). We therefore also monitored LC3-II and p62 in muscle samples from the experiment described above (Fig.…”
Section: Role Of Laforin In Glycogen Phosphorylation and Branching Dumentioning
confidence: 99%